2014
DOI: 10.1016/j.peva.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Moments of accumulated reward and completion time in Markovian models with application to unreliable manufacturing systems

Abstract: Performance evaluation models are used by companies to design, adapt, manage and control their production systems. In the literature, most of the effort has been dedicated to the development of efficient methodologies to estimate the first moment performance measures of production systems, such as the expected production rate, the buffer levels and the mean completion time. However, there is industrial evidence that the higher moments of the production output may drastically impact on the capability of managin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Angius et al proposed a method to analyze the cumulated output and the lot completion time moments in unreliable manufacturing systems characterized by general Markovian structures. Their outcomes showed that the proposed method could help analyze the dependency of the output variability and the service level of a system [23]. Mokhtari and Salmasnia addressed a neighborhood search algorithm for reducing the processing time of a multiple-machine manufacturing system.…”
Section: Technologymentioning
confidence: 99%
“…Angius et al proposed a method to analyze the cumulated output and the lot completion time moments in unreliable manufacturing systems characterized by general Markovian structures. Their outcomes showed that the proposed method could help analyze the dependency of the output variability and the service level of a system [23]. Mokhtari and Salmasnia addressed a neighborhood search algorithm for reducing the processing time of a multiple-machine manufacturing system.…”
Section: Technologymentioning
confidence: 99%
“…< l a t e x i t s h a 1 _ b a s e 6 4 = " h x X h c B u + f / H G x U l W 0 A / v p z K X O v A = " > A A A B 6 n i c b V B N S 8 N A E J 3 U r 1 q / q h 6 9 L B b B U 0 m 0 V H s r e P E i V L Q f 0 I a y 2 W 7 a p Z t N 2 N 0 I J f Q n e P G g i F d / k T f / j Z s 0 i F o f D D z e m 2 F m n h d x p r R t f 1 q F l d W 1…”
Section: M1mentioning
confidence: 99%
“…a path σ. A next formula Xϕ is satisfied by σ if ϕ is satisfied in the state which is next to the initial state of σ, i.e., σ [1]…”
Section: Probabilistic Model Checkingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these data, the stochastic distribution of the duration of each event reported in the event set is gathered, and the dynamic behaviour of the system is approximated by a continuous time Markov Chain. The evaluation of the main performance measures of the system, such as the average throughput, the average lead time and the distribution of the lot completion time for the given lots are calculated by using the method developed in [13]. The main innovation proposed by this module is the automatic generation of feasible material flow dynamics in the assembly system, starting from a static selection of resources in FAGs.…”
Section: Assembly System Configuration Modulementioning
confidence: 99%